Combustion characteristics of biomass briquettes - Chaney, Joel O. (2010)
Nearly half the worlds population is dependent on wood as their primary energy source. Therefore with deforestation becoming increasingly prevalent in many regions of the developing world, there is an urgent need to improve combustion efficiency of stoves or to find alternative fuels. Densification of loose biomass residues into briquettes is a means of upgrading the feedstock material. Briquettes are easier to store, more convenient to use and burn at a more steady and controlled rate than loose biomass. This investigation focuses on understanding some of their combustion characteristics and the relationship to the briquette design and manufacture process.